ChemInform Abstract: Palladium‐Catalyzed ortho‐Arylation of Carbamate‐Protected Estrogens. Issue 36 (August 2016) - Bedford, Robin B.; Brenner, Peter B.; Durrant, Steven J.; Gallagher, Timothy; Mendez‐Galvez, Carolina; Montgomery, Michelle
Abstract: Removal of the carbamate directing group is demonstrated.